Associations between prenatal diet quality and gestational weight gain. Issue 1 (March 2020) - Schlaff, Rebecca A; Baruth, Meghan; Deere, Samantha J; Boggs, Ashley; Odabasic, Anya
Background: Improving prenatal diet quality may promote appropriate gestational weight gain (GWG). Aim: To examine relationships between dietary quality in the second and third trimesters of pregnancy and GWG. Methods: Participants' ( n = 41) dietary intake was assessed at 14–20 and 35 weeks gestation via the Automated Self-Administered 24-h recall (ASA-24). Kilocalories and Healthy Eating Index (HEI-2015) scores were calculated and associations with GWG were explored via linear regression. Results: Participants reported consuming 2139 ± 719 and 2085 ± 704 kilocalories at 18 and 35 weeks, respectively. HEI-2015 total scores at 18 (55.6 ±12.6) and 35 weeks gestation (56.6 ± 14.1) indicated a need for improvement. Greens and beans component score at 35 weeks was the only diet quality score associated with GWG. Conclusions: GWG was not associated with most diet quality indices. However, vegetable intake may help to attenuate GWG. Future research should seek to elucidate relationships between GWG and dietary quality/intake to provide valuable insight for researchers and clinicians.